Dorsal Vagal Complex Modulates Neurogenic Airway Inflammation in a Guinea Pig Model With Esophageal Perfusion of HCl - Chen, Zhe; Sun, Lejia; Chen, Hui; Gu, Dachuan; Zhang, Weitao; Yang, Zifeng; Peng, Tao; Dong, Rong; Lai, Kefang (Frontiers in Physiology, 2018)
Neurogenic airway inflammation in chronic cough and bronchial asthma related to gastroesophageal reflux (GER) is involved in the esophageal-bronchial reflex, but it is unclear whether this reflex is mediated by central neurons. This study aimed to investigate the regulatory effects of the dorsal vagal complex (DVC) on airway inflammation induced by the esophageal perfusion of hydrochloric acid (HCl) following the microinjection of nuclei in the DVC in guinea pigs. Airway inflammation was evaluated by measuring the extravasation of Evans blue dye (EBD) and substance P (SP) expression in the airway. Neuronal activity was indicated by Fos expression in the DVC. The neural pathways from the lower esophagus to the DVC and the DVC to the airway were identified using DiI tracing and pseudorabies virus Bartha (PRV-Bartha) retrograde tracing, respectively. HCl perfusion significantly increased plasma extravasation, SP expression in the trachea, and the expression of SP and Fos in the medulla oblongata nuclei, including the nucleus of the solitary tract (NTS) and the dorsal motor nucleus of the vagus (DMV). The microinjection of glutamic acid (Glu) to enhance neuronal activity or exogenous SP in the DVC significantly potentiated plasma extravasation and SP release induced by intra-esophageal perfusion. The microinjection of γ-aminobutyric acid (GABA), lidocaine to inhibit neuronal activity or anti-SP serum in the DVC alleviated plasma extravasation and SP release. In conclusion, airway inflammation induced by the esophageal perfusion of HCl is regulated by DVC. This study provides new insight for the mechanism of airway neurogenic inflammation related to GER.